Collocational Restrictions of English Phrasal Verbs - Elgobshawi, Abdalla Elkheir (Journal of English Language and Literature (ISSN: 2368-2132), 2016)
Idioms and phrasal verbs constitute a highly considerable portion of the English vocabulary and their mastery is often indicated as a native like competence. They pose many difficulties to foreign learners because of their syntactic and semantic abnormalities. On semantic terms phrasal verbs, and idiomatic ones in particular, are viewed as phrases which do not correspond to their literal meanings. Syntactically they could be recognized by their idiosyncratic behavior which often defies the usual syntactic operations. The view of idioms and phrasal verbs as bits of frozen units provides only little possibility of syntactic and sematic flexibility. This paper attempts to trace the flexibility of the structure of phrasal verbs with reference to the collocational restrictions that govern their structures.